CONCEPTUAL APPROACHES TO EVALUATING THE EFFECTIVENESS OF INNOVATION IMPLEMENTATION AT ENTERPRISES - SHATILO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the peculiarities of the methods of evaluating the innovative development of the enterprise. It was determined that the main factors affecting the choice and combination of methods for assessing the innovative state of the enterprise for the purpose of developing a strategy for its innovative development and forming the management components of the mechanism for its implementation are: certain difficulties in determining the indicators that are included in the innovative enterprise development strategies; planning and forecasting terms; information security regarding the assessment of the possible influence of internal and external environmental factors on the further innovative activity of the enterprise; the results of the analysis of the relevant indicators in the retrospective, that is, in the previous period. It has been studied that to evaluate the development of innovative processes at enterprises, they are widely used analytical methods, in particular - statistical, expert assessment, including the method of morphological analysis. This is explained not only by the simplicity in the application of analytical methods, but also by the fact that thanks to these methods, on the one hand, it is possible to single out the characteristics of the studied component as part of a single whole in the general system, and on the other - to concentrate precisely on the study of the most important task in accordance with the set goal, taking into account the maximum possibilities for using all analytical approaches at the same time. It was found that for the analysis of internal and external environments, sub under the influence of which the enterprise functions, methods already known and effective in practical use can be involved - these are SWOT-analysis and PEST-analysis methods.